Language of Ukrainian Popular Medical Literature of 20-ies of the XX Century (Linguostylistic Studies, 2015)
The paper analyzes the features of Ukrainian language of popular science literature on medicine, which was printed by different publishers of Ukraine in 20-ies of the XX century. The history of popular medical publications and their subject matter, as well as the contribution of eminent educational movement in the development of Ukrainian language of scientific and popular discourse are reviewed. Particular attention is paid to the genre of popular medical pamphlets and definition of the characteristic features of subgenre of popular science scientific style Ukrainian literary language. These signs are the logic of presentation, its specification, including the elements of entertainment, use of terminological vocabulary with binding definitions, explanations, author's comments. Key words: popular science subgenre, educational literature, the popular medical publications, scientific and popular presentation, linguistic and stylistic features of popular scientific text. References